Adoption, diffusion and appropriation of double entry book-keeping in Mexico and Spain - Batiz Lazo, Bernardo; Hernández Borreguero, J. Julián; Maixé Altés, J. Carles; Nuñez Torrado, Miriam (América Latina en la Historia Económica, 2012)
<span lang="EN-US" style="line-height: 150%; font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-fareast-language: ES; mso-bidi-font-size: 10.0pt; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">There are conflicting and even contradictory claims as to when exactly double entry bookkeeping arrived to New Spain as well as its diffusion during the colonial era. Although we fail to present evidence from Mexican private enterprise, we address the apparent contradictions while putting forward the idea that the history of “modern” accounting practice in Latin America should be framed by developments in its former colonial power. Our conclusion is that the history of Latin American accounting should be wary of extrapolating everyday practice by interpreting bibliographic material and proceed to pay greater attention to the appropriation of accounting technology through the examination of surviving company documents as well as informal educational practices amongst organizations based in Spain and its colonies.